Implementation of Internet of Things-based Water Monitoring System in Vertical System based Crab Farming - Kusuma, Purba Daru; Widyantara, Helmy; Hariyanto, Muhammad Dwi; Putra, Seno Adi; Osmond, Andrew Brian (Universitas Negeri Semarang, 2025)
Crab is one of protein resource with high economic value. The vertical system is a crab farming method that provides several advantages including increasing space utility, minimizing crab mortality that is affected by cannibalism, and improving precision farming. As a continuation of 2024 research under the strategic collaboration (Katalis) scheme, a community service project has been conducted by implementing the Internet of Things (IoT) based water monitoring system to support precision farming in vertical system-based crab farming. Surabaya crab supermarket has become the partner in this community service. The objective of this activity is to implement this prototype in the real crab farming environment to investigate its effectiveness. This activity also gives experience for students at Telkom University that are involved in this project of implementing the developed precision farming system in the real environment despite the laboratories scale environment. Moreover, this project is also important to give insight from the crab farmer regarding the real problems that occur in crab farming. In the future, the system can be expanded by adding more features including the machine learning method to give predictions regarding the water quality and the growth of the crabs.